Peningkatan Unjuk Kerja Katalisator Zeolit Alam Bayah pada Reaksi Ketalisasi Gliserol - Nuryoto Nuryoto; Hary Sulistyo; Wahyudi Budi Sediawan; Indra Perdana (Dept. of Chemical Engineering, Diponegoro University, 2017)
Abstract IMPROVED PERFORMANCE OF BAYAH NATURAL ZEOLITE AS CATALYST ON REACTION OF GLYCEROL KETALIZATION. The catalyst has an important role for the rates of chemical reactions accelerating in orde to achieve the target product of reaction. Reactants mass transfer to the active sites of the catalyst is oftenbe anobstacle to reaching of this purpose, so that the catalyst performance becomes less than the maximum. The objective of this research was to observe how much effected the diameter size catalyst, stirring speed, and catalyst concentration in order to improved performance of Bayah natural zeolite catalyst on glycerol ketalization reaction based on glycerol conversion. The experiments were performed using a batch reactor, reaction temperature of 50oC, reactant ratio of 6:1 mol of acetone/mol of glycerol, reaction time of 90 minutes, diameter size catalyst from -18+25 until -60+70 mesh, catalyst concentration of 0-11% mass of glycerol, and stirring speed of 200-800 rpm. The results showed that the best conditions obtained at the diameter size catalyst of -40+45 mesh, catalyst concentration of 9% mass of glycerol, and stirring speed of 600 rpm by glycerol conversion reached of 60.92%. Keywords: glycerol; ketalization; performance; natural zeolite Abstrak Katalisator mempunyai peranan penting dalam mempercepat laju reaksi kimia untuk mencapai target produk reaksi yang diinginkan. Perpindahan massa reaktan ke sisi aktif katalisator seringkali menjadi kendala dalam mencapaimaksud tersebut, sehingga unjuk kerja katalisator menjadi kurang maksimal. Penelitian ini bertujuan untuk melakukan observasi seberapa besar pengaruh ukuran diameter katalisator, kecepatan pengadukan, dan konsentrasi katalisator dalam rangka meningkatkan unjuk kinerja katalisator zeolit alam Bayah pada reaksi ketalisasi gliserol berbasis konversi gliserol yang dihasilkan. Percobaan dilakukan dengan menggunakan reaktor batch, suhu reaksi 50oC, perbandingan pereaksi 6:1 mol aseton/mol gliserol,waktu reaksi 90 menit, ukuran diameter katalisator -18+25 sampai -60+70 mesh, konsentrasi katalisator 0-11% massa gliserol, dan kecepatan pengadukan 200-800 rpm. Hasil percobaan menunjukkan bahwa kondisi terbaik diperoleh pada ukuran diameter katalisator -40+45 mesh, konsentrasi katalisator 9% massa gliserol, dan kecepatan pengadukan 600 rpm dengan konversi gliserol mencapai 60,92%. Kata kunci: gliserol; ketalisasi; unjuk kerja; zeolit alam